Analysis of achievements for improvement in pedagogical competence of madrasah ibtidaiyah teachers - Ofi Rafiatul Jannah; Mohamad Ali (Himpunan Pengembang Kurikulum Indonesia, 2025)
This study aims to assess the educational and training needs to enhance the pedagogical competence of Madrasah Ibtidaiyah (MI) teachers in Bandung Regency. Recognizing the pivotal role of teachers in achieving educational objectives, this research focuses on the competencies related to curriculum development and instructional implementation. A quantitative descriptive method was employed, using surveys distributed via Google Forms to gather data from 340 teachers across 31 districts. The findings reveal that the overall pedagogical competence in curriculum development indicates a well-distributed mastery among the teachers. However, specific indicators such as understanding curriculum principles and organizing sequential learning materials scored lower, highlighting areas for improvement. Additionally, the competency in utilizing ICT in teaching was identified as a critical gap. This underscores the need for targeted training programs that emphasize modern educational technologies. The results suggest that continuous professional development and tailored training sessions are essential for enhancing the pedagogical skills of MI teachers, ensuring effective teaching and learning processes. Abstrak Penelitian ini bertujuan untuk menilai kebutuhan pendidikan dan pelatihan guna meningkatkan kompetensi pedagogik guru Madrasah Ibtidaiyah (MI) di Kabupaten Bandung. Menyadari peran penting guru dalam mencapai tujuan pendidikan, penelitian ini fokus pada kompetensi terkait pengembangan kurikulum dan pelaksanaan pembelajaran. Metode deskriptif kuantitatif digunakan, dengan survei yang disebarkan melalui Google Form untuk mengumpulkan data dari 340 guru di 31 kecamatan. Temuan menunjukkan bahwa kompetensi pedagogik secara keseluruhan dalam pengembangan kurikulum mengindikasikan penguasaan yang cukup merata di antara para guru. Namun, indikator spesifik seperti pemahaman prinsip kurikulum dan pengorganisasian materi pembelajaran secara runtut memiliki skor lebih rendah, menyoroti area yang perlu ditingkatkan. Selain itu, kompetensi dalam memanfaatkan TIK dalam pembelajaran diidentifikasi sebagai kesenjangan kritis. Hal ini menekankan perlunya program pelatihan yang menargetkan teknologi pendidikan modern. Hasil penelitian menunjukkan bahwa pengembangan profesional berkelanjutan dan sesi pelatihan yang disesuaikan sangat penting untuk meningkatkan keterampilan pedagogik guru MI, memastikan proses belajar mengajar yang efektif. Kata Kunci: kompetensi guru; kompetensi pedagogik; pelatihan; pembelajaran; pengembangan kurikulum